The Importance of Local Community Intelligence in Countering Terrorism: Speech/ Paper for NATO Centre of Excellence – Defence Against Terrorism (COE – DAT), Terrorism Experts Conference (TEC), Ankara, Turkey - 24- 25th October 2017 - Warnes, Richard (Honvédségi Szemle – Hungarian Defence Review, 2018)
Recent terrorist incidents in Europe and beyond, have highlighted the changing nature of the terrorist threat. Increasingly this has seen a shift from larger organised spectaculars to smaller self-contained cells and 'lone actors', using explosives and weaponry when accessible, but willing to launch attacks with 'cold weapons', such as knifes, and vehicles. While the previous larger attacks were often easier for the police and security forces to identify, because of the necessary communications, command and control, and associated organisational and financial signatures, recent attacks are more difficult to identify particularly when the operational planning is in the mind of a single 'lone actor'. Many such attacks are inspired, targeted, sanctioned and legitimised through the use of the social media and the internet. As a result, while the traditional 'top down' intelligence of national intelligence agencies re-mains critical, the role of 'bottom up' local community intelligence has become increasingly significant... No outsider will ever understand the complexities of a local community, and the individual actors within it, as somebody already inside that community... This is reflected in the growing focus in many countries on the development of 'human intelligence' (HUMINT) and increased emphasis on engagement with the community through community policing. Consequently this paper will examine both the changing nature of the terrorist threat and the concomitant importance of local community intelligence in countering terrorism.